Superwetting Janus membranes: focusing on unidirectional transport behaviors and multiple applications - Zhou, Hui; Guo, Zhiguang (Journal of materials chemistry. A, Materials for energy and sustainability, 2019)
It should be noted that the one-way transportation of liquids is of great significance to the separation or collection process and the manipulation of microfluids can effectively solve many practical problems, such as oil-water separation, fog-harvesting and so on. Fortunately, asymmetric wettability endows bioinspired Janus membranes (JMs) with special driving forces for unidirectional liquid transportation, which is of great potential in microfluidic manipulation. In this review, recent research advances in JMs are summarized with the focus on the development process, basic wetting properties and classifications of JMs. Based on different prepared materials, bioinspired special JMs can be divided into three categories as follows: polymeric Janus membranes, polymeric-inorganic Janus membranes and inorganic Janus membranes. Next, special attention is paid to the systematic physical mechanisms of unidirectional transport. Also outlined are current and potential applications in oil-water separation, membrane distillation, fog-harvesting, sensors and so on. Finally, a perspective on the future of bioinspired superwetting JM research and development is proposed. A comprehensive insight about Janus membranes is provided from their unidirectional transport behaviors and systematic physical mechanisms to asymmetric-wettability-dominated applications, which brings a new perspective to the manipulation of microfluids.